Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

.
Simplify the expression below
4(2x+8y+9)-3x+40
plz help


Sagot :

Answer:

5x+32y+76

Step-by-step explanation:

First, distribute.

4 x 2x = 8x

4 x 8y = 32y

4 x 9 = 36

Then, combine like terms.

8x - 3x = 5x

36 + 40 = 76

And that leaves 5x+32y+76

4(2x + 8y + 9) -3x + 40
= 8x + 32y + 36 - 3x + 40
= 8x - 3x + 32y + 36 + 40
= 5x + 32y + 76
So, in conclusion, the expression: 4(2x + 8y + 9) -3x + 40 simplified is: 5x + 32y + 76.
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.